ระบบตรวจติดตามสำหรับหน่วยชั้นเซลล์เชื้อเพลิงพีอีเอ็มขนาด 200 วัตต์ - พิทยา คนึงคิด (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
Although various designs have been introduced to improve the performance of a Proton Exchange Membrane fuel cell (PEMFC) stack system, fault conditions, such as drying or flooding, may still occur due to the complexity of the process. The development of a monitoring system which can detect these fault conditions is a key to operate PEMFC stack system effectively. In this study, a diagnostic system for a 200W PEMFC stack system has been developed by constructing models for determining the flooding and drying conditions inside the cell. Since the membrane resistance and pressure drop across the stack are important parameters for determining either drying or flooding conditions, the model-based monitoring scheme was proposed. Under typical operating condition, stack temperature and pressure, the differential pressure across the stack, and the load current and the voltage of PEMFC stack are measured. These measurement values will be fed into the models. The models will predict the important parameters of the cell. Pressure drop will be compared with its measurement values. If their differences are significant, flooding will be declared. On the other hand, cell drying will be declared if membrane water content drops below 4. The data acquisition system and the monitoring models have been developed under LabVIEW™ environment. The modeling results for pressure drop and ohmic resistance characteristics are in agreement with measured data. Finally, the analysis algorithm was applied into LabVIEW™ software.